A, The Manajemen Layanan Tenaga Pendidik di SMP Negeri 36 Makassar - Fadila Junilasari; Hasan; Ahmad Restani Syukron Thayyib (Irfani, 2026)
This study aims to describe the management of teacher services by education personnel at SMP Negeri 36 Makassar, as well as identify supporting and inhibiting factors in its implementation. The research method used is a descriptive qualitative approach. Data was collected through interviews, observations, and documentation with informants consisting of principals, teachers, and administrative staff. The data analysis applied the Miles and Huberman models, while the validity of the data was tested through triangulation of sources and techniques. The results of the study show that teacher service management includes three main aspects: attendance management, school Service Management, Teacher Services, Education Personnel.administration services, and lesson schedule preparation, which is implemented through planning, organizing, implementing, and evaluating functions. The main supporting factors include the commitment of the principal, collaboration between staff, and the adequacy of infrastructure. Meanwhile, the inhibiting factors are the limited quantity of staff, lack of training, the absence of standard Standard Operating Procedures (SOPs), and the operational system that is still manual. This study concludes that transformation towards digital-based management and strengthening the competence of human resources is indispensable to increase the effectiveness of education services.